A Comprehensive Systematic Review Comparing Perioperative Outcomes of Robotic-Assisted versus Laparoscopic Resection of the Anterior Liver Segments - Dita Oktaviani Ayuningtyas; Ika Fitriana Setyaningtias (The Indonesian Journal of General Medicine, 2026)
Introduction: Minimally invasive liver surgery (MILS) is the contemporary standard for lesions in the anterior liver segments (II, III, IVb, V, VI), where the parenchymal transection plane is directly accessible. Robotic advantages in posterosuperior segments and major hepatectomy are established, yet its incremental value in the comparatively "easy" anterior segments remains contested. Methods: The study strictly adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines comparing robotic (RLR) versus laparoscopic (LLR) liver resection in anterior segments. Risk of bias assessed with ROBINS-I and RoB 2. Sixteen perioperative outcomes were synthesised narratively with direction-of-effect vote counting. Results: Twenty-three studies (>20,000 hepatectomies) were included. In the largest anterior-segment analysis (1,401 matched pairs), RLR had lower blood loss (75 vs 100 mL, P<0.001), lower transfusion (3.1% vs 5.4%, P=0.003), lower major morbidity (2.5% vs 4.6%, P=0.004), lower conversion (1.2% vs 4.5%, P<0.001), and shorter stay (4 vs 5 days, P<0.001), but higher 30-day readmission (3.5% vs 2.1%, P=0.042). A second international cohort (1,505 pairs) confirmed higher textbook outcome (78.3% vs 71.8%, P<0.001), lower blood loss, and lower morbidity. Direction-of-effect: robotic superior for conversion (16/18 studies) and blood loss (14/21), laparoscopic superior for operative time (13/21) and cost (7/7). Mortality, bile leak, liver failure, R0, and survival were equivalent. The single RCT found no quality-of-life difference. Discussion: In the anterior segments, robotics yields statistically significant but clinically modest gains, concentrated in haemostasis and conversion avoidance. Benefit magnitude is markedly attenuated relative to posterosuperior segments, consistent with a ceiling effect: laparoscopy in the anterolateral liver is already mature with low conversion and morbidity. The economic penalty of robotics is uniform and substantial. Conclusion: Robotic anterior-segment resection is safe and oncologically non-inferior, with advantages in blood loss, conversion, morbidity, and length of stay, but longer operative time and higher cost. Laparoscopy remains a highly cost-effective default; robotics is best justified in cirrhosis, reoperative surgery, and institutional MILS programme development.